Feasibility of Wave Intensity Analysis in Patients With Conotruncal Anomalies Before and After Pregnancy: New Physiological Insights? - Ordonez, Maria Victoria; Neumann, Sandra; Caputo, Massimo; Curtis, Stephanie; Biglino, Giovanni (Frontiers in Pediatrics, 2021)
Background: Conotruncal anomalies (CTA) are associated with ongoing dilatation of the aortic root, as well as increased aortic stiffness that may relate to intrinsic properties of the aorta. Pregnancy hormones lead to hemodynamic changes and remodeling of the tunica media, resulting in the opposite effect i.e. increasing distensibility. These changes normalize post-pregnancy in healthy women but have not been fully investigated in CTA patients. Methods: We examined aortic distensibility and ventriculo-arterial coupling before and after pregnancy using cardiovascular magnetic resonance (CMR)-derived wave intensity analysis (WIA). Pre- and post-pregnancy CMR data were retrospectively analyzed. Aortic diameters were measured before, during and after pregnancy by cardiac ultrasound, and before and after pregnancy by CMR. Phase contrast MR flow sequences were used for calculating wave speed (c) and intensity (WI). A matched analysis was performed comparing results before vs. after pregnancy. Results: Thirteen women (n=5 transposition of the great arteries, n=6 tetralogy of Fallot, n=1 double outlet right ventricle, n=1 truncus arteriosus) had 17 pregnancies. Median time between delivery and second CMR was 2.3 years (range: 1-6 years). Aortic diameters increased significantly after pregnancy in nine (n=9) patients by a median of 4±2.3mm (range: 2-7.0 mm, p=0.01). There was no difference in c pre-/post-pregnancy (p=0.73), suggesting that increased compliance, typically observed during pregnancy, does not persist long term. A significant inverse relationship was observed between c and heart rate (HR) after pregnancy (p=0.01, r=0.73). There was no significant difference in cardiac output, aortic/pulmonary regurgitation, or WI peaks pre-/post-pregnancy. Conclusions: WIA is feasible in this population and could provide physiological insights in larger cohorts. Aortic distensibility and wave intensity did not change before and after pregnancy in CTA patients, despite an increase in diameter, suggesting that pregnancy did not adversely affect coupling in the long-term.